(untitled) (Communications in Computational Physics, 2009)
Usually extended two-phase capillary pressures are used in three-phase simulations, because three-phase capillary pressures are not possible or hard to measure. In this work three-phase capillary pressure surfaces are created by at pore network model. The input parameters to this network model are found by matching two-phase capillary pressure curves. This matching is done with a slightly modified EnKF routine. Tables with three-phase capillary pressures are created and used as input to flow simulations.